The insecticidal potential of Foeniculum vulgareMill., Pimpinella anisum L. and Caryophillus aromaticus L. to control aphid on kale plants - P. S. R. LUCCA; L. H. P. NÓBREGA; L. F. A. ALVES; C. T. A. CRUZ-SILVA; F. P. PACHECO (Universidade Estadual Paulista, 2015)
ABSTRACTThe use of natural substances for pest control in agriculture is, economically, a viable option and has benefits for both the humanbeing and the environment, due to its low persistence and toxicity. Thus, this trial aimed on determining the insecticidal potential of the extracts and essential oils of fennel (Foeniculum vulgare Mill.), anise (Pimpinella anisum L.) and clove (Caryophillus aromaticus L.) to control Brevicoryne brassicae L. in kale (Brassica oleracea var. acephala DC.). The treatments were: fennel, anise, cloves extracts at 10%; fennel, anise, cloves oils at 1% and control with distilled water. The mortality tests were carried out with aphids in laboratory, with three replications, after 1, 12, 24, 48 and 72 hours. During laboratory trials , it was found out that fennel oil at 1% showed the best rate of mortality on aphid nymphs (70% at 72 h), followed by clove extract at 10% with 37% mortality. Tests in pots were only carried out only with cloves extracts at 10% and fennel oil at 1% treatment, in which such efficiency was alsoindicated on aphid nymphs.